Human rights and adolescence - Bhabha, Jacqueline (Pennsylvania studies in human rights., 2014)
"Human Rights and Adolescence presents a multifaceted inquiry into the global circumstances of adolescents, focusing on the human rights challenges and socioeconomic obstacles young adults face. Contributors use new research to advance feasible solutions and timely recommendations for a wide range of issues spanning all continents, from relevant international legal norms to neuropsychological adolescent brain development, gender discrimination in Indian education to Colombian child soldier recruitment, stigmatization of Roma youth in Europe to economic disempowerment of Middle Eastern and South African adolescents. Taken together, the research emphasizes the importance of dedicated attention to adolescence as a distinctive and critical phase of development between childhood and adulthood and outlines the task of building on the potential of adolescents while providing support for the challenges they experience"--Publisher